Fatigue equation for asphalt mixture under low temperature and low loading frequency conditions. (30th June 2019) - Lv, Songtao; Xia, Chengdong; Liu, Chaochao; Zheng, Jianlong; Zhang, Fangchao
Highlights: The strength and fatigue tests of asphalt mixtures were implemented. The evolution patterns of strength with loading rate were revealed. The unified fatigue model of asphalt mixtures was established. The behavior of thermal fatigue and strength failure was integrated. Abstract: In order to reveal the thermal fatigue behavior of asphalt mixtures under low temperature conditions, the four-point bending beam tests of strength and fatigue were carried out. The asphalt mixtures are typical viscoelastic materials whose fatigue properties are significantly influenced by low loading frequency. Thus, the fatigue tests under low loading frequency were used to simulate the thermal fatigue of asphalt mixtures. Based on the nominal stress ratio (not considering the effect of loading rate on the strength value) and the real stress ratio (the strength value corresponding to the loading rate of fatigue test), the fatigue equations of asphalt mixtures under low temperature and low frequency conditions were established. The flexural strengths of the four-point bending beam tests at different loading rates at 0 °C, −10 °C and −20 °C were studied. The results show that the flexural strength of asphalt mixtures expresses a power function on the pattern of variation with the loading rates. The intersection of fatigue curve characterized by the nominal stress ratio and the abscissa axis is much larger than 1. The fatigue curve based on the nominal stress ratio cannot be extended to fatigue failure point (1, 1). But the fatigue curve characterized by the real stress ratio can be extended to the strength failure point, whose fatigue life is 1. So, the behavior of strength failure and fatigue failure was integrated. The uniform characterization model of fatigue equations for asphalt mixture under low temperature and low loading frequency conditions was realized, which means that the fatigue equations and curves under different loading frequencies could be characterized by one equation and one curve. The results can provide a theoretical basis for predicting the thermal fatigue performance of asphalt mixtures under low temperature conditions more accurately.